Developing ‘Adaptive Reuse Strategies’ for Heritage Buildings: A Case Study of Agios Panteleimon Monastery in Cyprus - Günçe, Ka?an; Mısırlısoy, Damla (Peter Lang Publishing Group, 2021)
Heritage buildings play a significant role in transmitting ones culture to the generations to come. Adaptive reuse strategies can become a practical solution in preserving national heritages once their original roles diminish in time. When applying adaptive reuse strategies, the most crucial stage is to determine an appropriate function. In order to decide the most appropriate adaptive reuse strategy for the heritage buildings all the factors must be taken into consideration holistically. The aim of the study is to propose a method that can be used in developing adaptive reuse strategies. As the method, a proposed model, which is developed for adaptive reuse strategies, was investigated. Secondly, The Agios Panteleimon Monastery in Cyprus was observed through site survey as a case study and then, a matrix of various adaptive reuse strategies and alternatives have been formulated and discussed. The aim of the proposed method is, therefore, of two-folds: to support decision makers in adaptive reuse projects and to inspire architects, designers, engineers, urban planners and restoration experts practicing strategies for adaptive reuse projects. Additionally, the method can be used as a guide for further researches in determining adaptive reuse strategies. In adaptive reuse decision-making process, it is important to perform a detailed analysis of the heritage building. Incorporated onsite surveys are essential in understanding the behaviour of the heritage building, its background and the needs of the area. In-depth site surveys will ensure a full understanding of the area yielding a better choice of new use for each heritage building if their physical and original values are to be preserved. The continuity of the heritage buildings rely upon the correct choices made. In determining a new function, the factors that impact the adaptive-reuse-strategies need to be evaluated in terms of perspective and adaptability. © Peter Lang GmbH Internationaler Verlag der Wissenschaften Berlin 2021 All rights reserved.
Keywords: Adaptive reuse strategies; Decision-making; Heritage buildings; Holistic approach